Pengaruh biaya produksi terhadap laba usaha pada UD Sukamaju Kabupaten Majalengka - Hidayati, Fika; Gita Kartika Sari (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The purpose of this study was to determine the respondents' responses to customer relationship marketing at UD Sukamaju, Majalengka Regency, to find out how the level of consumer loyalty at UD Sukamaju, Majalengka Regency, and to find out how much influence customer relationship marketing had on consumer loyalty at UD Sukamaju, Majalengka Regency. The data collection method in this study was a questionnaire filled out by respondents, namely consumers of UD Sukamaju, Majalengka Regency. Sampling as many as 99 respondents in this study using a simple sampling method. The independent variable in this research is customer relationship marketing, while the dependent variable is consumer loyalty. The analysis used in this research includes analysis of validity test, reliability test, linear regression analysis, correlation analysis and coefficient of determination, hypothesis testing t-test. There is a significant influence between Relationship marketing and consumer loyalty at UD Sukamaju, Majalengka Regency. The results of the calculation of the regression coefficients based on the research data obtained can be written in the estimated regression equation as follows Y = 0.88 + 0.48 X. The results of the calculation of the correlation value are 0.7322. This value shows the strength of the relationship between the quality of customer service and customer loyalty at UD Sukamaju, Majalengka Regency, Majalengka Branch. Included in the strong group. The coefficient of determination for the influence of customer service quality on consumer loyalty at UD Sukamaju, Majalengka Regency, Majalengka Branch was 53.61%. So 53.61% of changes in consumer loyalty at UD Sukamaju, Majalengka Regency, Majalengka Branch can be explained, while the remaining 46.39% is influenced by other factors not examined.